"Bluewashing" the Firm? Voluntary Regulations, Program Design, and Member Compliance with the United Nations Global Compact. Issue 1 (27th October 2014) - Berliner, Daniel; Prakash, Aseem
<x xml:space="preserve">Abstract</x> Voluntary programs have emerged as important instruments of public policy. We explore whether programs lacking monitoring and enforcement mechanisms can curb participants' shirking with program obligations. Incentive‐based approaches to policy see monitoring and enforcement as essential to curb shirking, while norm‐based approaches view social mechanisms such as norms and learning as sufficient to serve this purpose. The United Nations Global Compact (UNGC), a prominent international voluntary program, encourages firms to adopt socially responsible policies. Its program design, however, relies primarily on norms and learning to mitigate shirking. Using a panel of roughly 3, 000 U.S. firms from 2000 to 2010, and multiple approaches to address endogeneity and selection issues, we examine the effects of Compact membership on members' human rights and environmental performance. We find that members fare worse than nonmembers on costly and fundamental performance dimensions, while showing improvements only in more superficial dimensions. Exploiting the lack of monitoring and enforcement, UNGC members are able to shirk: enjoying goodwill benefits of program membership without making costly changes to their human rights and environmental practices.